Prevalence, risk factors and hepatitis B immunization: helping fill the gap on hepatitis B epidemiology among homeless people, Goiânia, Central Brazil - Carvalho,Paulie Marcelly Ribeiro dos Santos (2017)
Data are limited in Brazil on hepatitis B infection among homeless individuals, a marginalized population with high risk of sexually transmissible infections (STI), including hepatitis B. The aim of this study was to investigate hepatitis B epidemiology in homeless persons lodged in a public shelter in Goiânia, Central Brazil. From August 2014 to June 2015, 353 individuals were interviewed and tested for markers of HBV infection. Overall HBV prevalence was 21.8% (95%CI: 17,82-26,41), and 19,5% (95%CI: 15,75-24,0) showed a serological profile of previous HBV vaccination. Older individuals (> 50 years), blacks, and homosexuals or bisexuals showed increased exposure to HBV. The low frequency of individuals immunized against HBV, high social vulnerability, and risk behaviors emphasize the need for health services administrators to provide more opportunities for HBV vaccination in this target population.